The Effect of Career Development on Employee Performance in PT. Dwi Indah Jakarta - Herliani, Lisda; Irawan, Pristanto Ria; Ardianto, Rian (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this study is to determine career development of the performance of PT. Dwi Indah Jakarta. This study used quantitative descriptive methods with data collection techniques through the distribution of questionnaires, and library data. In this study using a saturated sampling method used a total of 31 employees of PT. Dwi Indah Jakarta, using simple linear regression data analysis techniques. The results of this study show that there is an influence between career development on the performance of PT. Dwi Indah Jakarta has a strong positive influence and has an influence contribution of 55.2% on employee performance variables. The results of this study are expected to contribute to future research.